THE RULING ON WISHING MERRY CHRISTMAS TO NON-MUSLIMS: AN ANALYSIS OF M. QURAISH SHIHAB'S INTERPRETATIONS - Andiko, Toha; Mutia, Isna; Nazaryani, Nazaryani (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The debate on wishing Merry Christmas to non-Muslims has become a major focus in discussions among Muslims in Indonesia. The diverse perspectives on this issue reflect the tension between religious principles and the complex socio-cultural demands of a multicultural society. This study examines M. Quraish Shihab's views on the ruling of wishing Merry Christmas to non-Muslims, focusing on his inclusive interpretation, tolerance, and respect for religious diversity. This research employs a qualitative approach and uses hermeneutical analysis to explore the Qur'anic texts that form the basis of Quraish Shihab's views. The findings show that Quraish Shihab supports the practice of wishing Merry Christmas, considering it permissible in the context of strengthening social relationships, provided it is done with a clear intention and without acknowledging theological aspects that contradict Islam. A comparison with the views of other scholars, such as Ibn Taymiyyah, Yusuf al-Qaradawi, and Ahmed Kutty reveals a variety of opinions on this issue. The study concludes that Quraish Shihab's inclusive approach in his interpretation has made a valuable and positive contribution to understanding and applying Islamic values in a pluralistic society like Indonesia, while also emphasizing the importance of interfaith dialogue and maintaining harmonious social relationships.